Psychological reactance impacts ratings of pediatrician vaccine-related communication quality, perceived vaccine safety, and vaccination priority among U.S. parents - Stacey R. Finkelstein; Wendy Attaya Boland; Beth Vallen; Paul M. Connell; Gary D. Sherman; Kristen A. Feemster (Taylor & Francis Group, 2020)
Physician communication surrounding vaccination is important in driving patient compliance with schedules and recommendations, but patient psychological factors suggest that communication strategies may have differential effects on patients. This paper investigates how psychological reactance, defined as an individuals' propensity to restore their autonomy when they perceive that others are trying to impose their will on them, impacts perceptions about physician communication and perceptions and prioritizations of vaccination. We propose and describe the results of a study that was conducted to assess the relationship between individual differences in reactance, perceived quality of pediatrician communication, perceptions of vaccination safety, and vaccination prioritization using a sample of parents. We recruited 300 parent participants via the online platform Prolific Academic in which they completed a computer-mediated survey. Results show that compared to those who are low in psychological reactance, those high in psychological reactance place less of a priority on vaccination, and that this relationship is driven by evaluations of physician communication quality and perceived vaccine safety. Our findings suggest that physicians should not adopt a one-size-fits-all approach when interacting with patients and should tailor messaging to patients based on psychological factors including reactance.